PATOFISIOLOGI SKIATIKA - Thomas Eko P* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION THE ANCIENT GREEKS WERE FAMILIAR WITH SCIATIC NEURALGIA AND USED THE TERM SCIATICA TO DESCRIBE PAIN OR FELT AROUND THE HIP OR THIGH SCIATICA IS A RELATIVELY COMMON CONDITION WITH A LIFETIME INCIDENCE VARYING FROM 13 TO 40 THE CORRESPONDING ANNUAL INCIDENCE OF AN EPISODE OF SCIATICA RANGES FROM 1 TO 5 FORTUNATELY THE MAJORITY OF CASES RESOLVE SPONTANEOUSLY WITH SIMPLE ANALGESIA AND PHYSIOTHERAPY HOWEVER THE CONDITION HAS THE POTENTIAL TO BECOME CHRONIC AND INTRACTABLE WITH MAJOR SOCIOECONOMIC IMPLICATIONS THE MOST COMMON CAUSE OF SCIATICA IS HERNIATED DISC BESIDE INFECTION AND MALIGNANCY